1990
DOI: 10.1152/jappl.1990.68.4.1568
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changes in osmolarity on isolated human airways

Abstract: The effects of hypo- and hyperosmolarity on the function of isolated human airways were studied. Changes in osmolarity induced an increasing bronchoconstriction that was proportional to the magnitude of the change in osmolarity. Hypertonicity-induced airway narrowing resulted when buffer was made hypertonic with sodium chloride or mannitol but not with urea. The airways showed no tachyphylaxis to repetitive exposure to hypo- and hypertonic buffer of 200 and 600 mosM, respectively. The bronchoconstriction was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 0 publications
3
19
1
Order By: Relevance
“…8a,b). This fits with results obtained by Jongejan et al (1990) showing that 450 mOsm is the highest osmolarity that does not cause osmotic shrinkage. When the cells were allowed to recover in 295 mOsm EMEM for 1 hour subsequent to hyperosmotic stress at 700 mOsm, the morphological recovery was remarkable.…”
Section: Teer Measurementssupporting
confidence: 92%
“…8a,b). This fits with results obtained by Jongejan et al (1990) showing that 450 mOsm is the highest osmolarity that does not cause osmotic shrinkage. When the cells were allowed to recover in 295 mOsm EMEM for 1 hour subsequent to hyperosmotic stress at 700 mOsm, the morphological recovery was remarkable.…”
Section: Teer Measurementssupporting
confidence: 92%
“…In bronchial smooth muscle, similar observations about different modes of action of hyper-and hyposmolar solutions have also been reached [13]. In hyperosmolar solutions the changes to phasic and baseline tension were a function of osmolarity per se, as similar responses were observed irrespective of the osmolyte used, and were not accompanied by significant alterations to intracellular [Ca 2+ ] in isolated detrusor myocytes.…”
Section: Discussionsupporting
confidence: 63%
“…It has been reported that hypotonic stimulation induces airway smooth muscle contraction in human airways in vivo and in vitro (2,3,11,20,31). In the present studies, we show that hypotonic solution-induced airway contraction is dependent on the extracellular Ca 2ϩ in both human and guinea pig airways.…”
Section: Discussionmentioning
confidence: 99%
“…Hypotonic solution also contracts isolated human airways (11,20). However, the mechanism for hypotonic stimulation-induced airway contraction is not clear.…”
mentioning
confidence: 99%